Solvent and Heating Duration Effects on the Formation of Local Pyrophyllite PEG-4000 Hybrid Materials - Siti Mutrofin; Wanda Ainun Shabiya; Hanisah Kamilah (UNIVERSITAS SEBELAS MARET (UNS), 2025)
Hybrid materials are new materials formed by combining two or more components to produce enhanced and distinct properties from the individual constituents. One example is the hybrid system of pyrophyllite and PEG 4000. This hybrid has not been reported and has potential for various applications. Local (Sumbermanjing) pyrophyllite-PEG 4000 hybrid was synthesized using casting and sol-gel methods with variations in solvent type (demineralized water, methanol, acetone) and heating time (1, 1.5, 2 hours) at a temperature of 100 – 105 ℃. Acetone produced the highest yield (34.89%) due to superior solvent-material interactions, while two-hour heating achieved maximum yield (36.20%) through enhanced intermolecular bonding. Statistical analysis confirmed significant differences in solvent variations, while heating time showed no significant effect. FTIR characterization revealed specific functional groups O–H stretching (Al-–OH linkage) at 3673.92 cm⁻¹, O–H stretching (3487.09 cm⁻¹), C–O stretching (1103.89 cm⁻¹), and Al–-OH bending vibration at 841.46 cm⁻¹, thus confirming successful hybrid formation. Melting point analysis showed 128.13 °C (1 hour heating hour) and 124.83 °C (2 hours heating time), indicating new material formation.